ANALISIS MANAJEMEN SYARIAH PENGARUH KINERJA KEUANGAN PT. AMARTHA MIKRO FINTECH PADA MASA PANDEMI COVID-19 TERHADAP DANA CORPORATE SOCIAL RESPONSIBILITY (CSR) - Setiawan, Harly; Thantawi, Tubagus Rifqy; Mursyidah, Azizah (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
Covid-19 is a problem for the Indonesian nation and the world. The problem is that the Indonesian and world economies are hampered. This influence also occurs in companies. Companies need to recalculate their finances in order to continue their existence. Company owners must be able to analyze their company's financial reports to find out the extent of their company's financial performance. One tool for analyzing financial reports is to use the Return of Assets (ROA), Return of Equity (ROE) and Net Profit Margin (NPM) ratios. Likewise with PT Amartha Mikro Fintech. At the same time, PT Amartha Mikro Fintech remains committed to implementing its Corporate Social Responsibility (CSR). However, it is necessary to examine the influence of financial performance on PT Amartha Mikro Fintech's CSR funds. Through this research, an analysis of the financial performance of PT Amartha Mikro Fintech and its influence on CSR funds was carried out. This research uses quantitative methods with multiple linear regression analysis. There are three independent variables for financial performance, ROA, ROE, and NPM, as well as the dependent variable Corporate Social Responsibility (CSR). Based on research results, during the Covid-19 pandemic, PT Amartha Mikro Fintech's financial performance had effect on its CSR funds.